Pengaruh Gaya Kepemimpinan dan Kompensasi Terhadap Kepuasan Kerja: Studi Kasus pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaan di Malang Raya - Sinollah, Sinollah; Ubaitulloh, Muhammad (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2021)
This study aims to determine and analyze the influence of leadership style and compensation on job satisfaction at the Employment of Badan Penyelenggara Jaminan Sosial Ketenagakerjaan in Malang Raya. To achieve this goal, this study uses quantitative methods using multiple linear regression analysis. This study uses the dependent variable, namely Leadership Style and Compensation. While the independent variable is satisfaction. The sample used in this study is 44 which is the entire population. The results showed that leadership style and compensation did not have a significant effect either partially or simultaneously on job satisfaction at Badan Penyelenggara Jaminan Sosial Ketenagakerjaan di Malang Raya in Malang Raya